2022
DOI: 10.1021/acsami.2c17628
|View full text |Cite
|
Sign up to set email alerts
|

Inner Lithium Fluoride (LiF)-Rich Solid Electrolyte Interphase Enabled by a Smaller Solvation Sheath for Fast-Charging Lithium Batteries

Abstract: Fast-charging lithium-ion batteries (LIBs) have been severely hampered by the slow development of their electrolytes. Herein, we demonstrate that the size effect of solvent sheath would pose a great effect on the fast-charging performance of LIBs. Three similar ethers, including diethyl ether (DEE), dipropyl ether (DPE), and dibutyl ether (DBE), were mixed with 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and lithium bis(fluorosulfonyl)imide (1 M) to form an electrolyte for fast-charging LIBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In 2023, Li et al have demonstrated that the size effect of solvent shell has a great influence on the fastcharging performance of Li batteries (Figure 14b). [116] The results showed that the stable and suitably sized terpolymer graphite intercalation compounds (GICs) in the graphite anode is formed in diethyl ether (DEE) /LiFSI electrolyte, and generate LiF-rich SEI internally.…”
Section: Electrolyte Improvementmentioning
confidence: 99%
“…In 2023, Li et al have demonstrated that the size effect of solvent shell has a great influence on the fastcharging performance of Li batteries (Figure 14b). [116] The results showed that the stable and suitably sized terpolymer graphite intercalation compounds (GICs) in the graphite anode is formed in diethyl ether (DEE) /LiFSI electrolyte, and generate LiF-rich SEI internally.…”
Section: Electrolyte Improvementmentioning
confidence: 99%
“…The Li-ion diffusion in LiF crystals is slow, which conflicts with the high ionic conductivity of LiF-rich SEI. [33,34] However, it claimed that the distribution of inorganic components in SEI is with nano-tiny grain and that there exists tremendous grain boundaries. The Li-ion diffuses much faster in the grain boundary than in the bulk of inorganic components.…”
Section: Introductionmentioning
confidence: 99%